208:poster Cost-effectiveness of integrated treatment for hepatitis C virus (HCV) among people who inject drugs in Norway: an economic evaluation of the INTRO-HCV trial. (28th April 2022) - Lim, Aaron G; Aas, Christer Frode; Çağlar, Ege Su; Vold, Jørn-Henrik; Fadnes, Lars Thore; Johansson, Kjell Arne; Vickerman, Peter
Abstract : Introduction: People who inject drugs (PWID) have the highest burden of hepatitis C virus (HCV) globally, but are often undertreated due to stigma and lack of access to services. The INTRO-HCV randomised control trial conducted in Norway over 2017-2019 found that integrating HCV treatment, using direct-acting antivirals (DAAs), among PWID in community settings improved treatment outcomes, but did not compare longer-term health economic benefits. This study analyses the cost-effectiveness of integrated treatment compared to standard referral pathway. Methods: A health state transition Markov model of HCV disease progression and treatment was developed based on the INTRO-HCV trial. Treatment unit costs and health-related quality of life outcome data were derived from the trial and used to parameterise the model. The incremental cost-effectiveness ratio (ICER) was calculated in terms of cost per quality-adjusted life year (QALY) gained from the health provider's perspective over a lifetime horizon and compared against a conventional (NOK 500, 000) willingness-to-pay (WTP) threshold for Norway. Probabilistic and univariate sensitivity analyses were undertaken, focussing on DAA price reductions. Results: Compared to standard treatment, integrated treatment resulted in an ICER of NOK 213, 498/QALY gained, with 90.8% probability of being cost-effective against the conventional WTP threshold. Sensitivity analyses suggest that cost of DAA medications strongly affected the ICER, with 30% lower DAA price resulting in integrated treatment having an ICER of NOK 91, 825/QALY gained and 98.9% probability of being cost-effective. A 60% lower DAA price led to negative ICER of NOK -20, 607/QALY gained, with 100% probability of being cost-effective and 66.8% probability of being cost-saving. A 90% lower DAA price had negative ICER of NOK -140, 205/QALY gained and 100% probability of cost-saving. Discussion: Integrating HCV treatment for PWID in community settings is likely to be highly cost-effective and may become cost-saving even with moderate reductions in DAA price.